CALCIUM ISOTOPE FRACTIONATION IN MODERN SCLERACTINIAN CORALS - Bohm F.; Gussone N.; Eisenhauer A.; Dullo W.C.; Reynaud S.; Paytan A. (My University, 2006)
The 44Ca/40Ca ratios of cultured (Acropora sp.) and open ocean (Pavona clavus, Porites sp.) tropical reef corals are positively correlated with growth temperature. The slope of the temperature-fractionation relation is similar to inorganic aragonite precipitates. However, ?44/40Ca of the coral aragonite is offset from inorganic and sclerosponge aragonite by about +0.5?. This offset can neither be explained by the very fast, biologically controlled calcification of scleractinian corals, nor as a consequence of calcification from a partly closed volume of fluid. As corals actively transport calcium through several cell layers to the site of calcification, the most likely explanation for the offset is a biologically induced fractionation. Our results indicate a limited use of Ca isotopes in scleractinian corals as temperature proxy.
Keywords: ARAGONITE; CALCIFICATION; CALCIUM; CORAL; ISOTOPIC FRACTIONATION; ACROPORA; ANTHOZOA; PAVONA CLAVUS; PORITES; SCLERACTINIA